Spol in jezik na robu pameti - Šorli, Mojca (Slovenščina 2.0, 2019)
The present text revisits the public debate that followed the passing of "Decision 41" by the Senate of the Faculty of Arts, University of Ljubljana, on a language policy introducing gender-sensitive language use in the Faculty's administra-tive documents. The debate attracted public attention and media interest for several months, culminating in a Round Table on Gender and Language, which took place at the UL Faculty of Arts almost exactly one year ago, on 23 October 2018. While re-evaluating the views expressed in the debate from a temporal distance, this paper is an attempt to continue the debate on gender categories and gender identities, focusing on androcentricity in language. In addition to highlighting the theoretical background that is (or should be) the driving force of the debate, we also performed a simple statistical analysis of the collected opinions and responses by media representation and gender representation. In the qualitative part of the analysis, we were primarily interested in which (apparent) expert and ideological oppositions fuelled the specific rhetoric and discourse adopted in the debate.
Keywords: androcentricity; androcentričnost; discourse; diskurz; gender-sensitive language use; spolno občutljiva raba jezika